2015
DOI: 10.1016/j.socscimed.2015.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Puberty and perimenopause: Reproductive transitions and their implications for women's health

Abstract: This scoping review synthesizes existing research on two major transitions in females’ lives: puberty and perimenopause. These two periods of vast physiological change demarcate the beginning and the end of the reproductive life cycle and are associated with major neuroendocrine reorganization across two key systems, the hypothalamic-pituitary-gonadal (HPG) axis the hypothalamus-pituitary-adrenal (HPA) axis. Despite growing evidence suggesting that the timing and experience of puberty and perimenopause are rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 177 publications
(209 reference statements)
0
59
0
2
Order By: Relevance
“…Although early menarche has been associated with adult obesity and metabolic risk factors [7,26] , the associations remained significant after adjustment for these factors in the present and previous studies [7,8] . It has been suggested that early menarche may not predict an unfavorable cardiovascular profile, but may reflect negative metabolic imprinting during pre-pubertal life [5,26] . For example, girls with their weights on the higher side tend to experience menarche at younger ages [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although early menarche has been associated with adult obesity and metabolic risk factors [7,26] , the associations remained significant after adjustment for these factors in the present and previous studies [7,8] . It has been suggested that early menarche may not predict an unfavorable cardiovascular profile, but may reflect negative metabolic imprinting during pre-pubertal life [5,26] . For example, girls with their weights on the higher side tend to experience menarche at younger ages [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, girls with their weights on the higher side tend to experience menarche at younger ages [27][28][29] . However, child or adolescent body weight has not been measured yet [5] . If elevated childhood weight contributes to early menarche, which in turn leads to the incidence of stroke as suggested [5] , then preventing childhood obesity could well become a strategy for stroke prevention in later life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Younger menarcheal age has also been related prospectively to a host of cardiovascular risk factors in adolescence and adulthood as well as to a worsening of these risk factors over time (Feng et al, 2008; Frontini et al, 2003; Hoyt & Falconi, 2015; Hulanicka et al, 2007; Kivimaki et al, 2008; Lakshman et al, 2009; Pierce, Kuh, & Hardy, 2010; Remsberg et al, 2005; Widén et al, 2012). For example, girls with earlier menarche, defined at the 25 th percentile or less (11.9 years), experienced greater increases in insulin, glucose, systolic blood pressure (SBP), and diastolic blood pressure (DBP) over the 13-year study period (ages 8 to 21); these changes were observed independently of correlated changes in body composition (marked by indicators: fat-free mass and percent body fat) (Remsberg et al, 2005).…”
Section: Pubertal Timing and Healthmentioning
confidence: 99%